Transforming growth factor β‐mediated site‐specific Smad linker region phosphorylation in vascular endothelial cells. (14th October 2014) - Kamato, Danielle; Rostam, Muhamad Ashraf; Piva, Terence J.; Babaahmadi Rezaei, Hossein; Getachew, Robel; Thach, Lyna; Bernard, Rebekah; Zheng, Wenhua; Little, Peter J.; Osman, Narin
Abstract Objectives Transforming growth factor (TGF)‐β regulates the function of vascular endothelial cells and may be involved in endothelial dysfunction. The canonical TGF‐β pathway involves TGF‐β receptor‐mediated carboxy‐terminal phosphorylation of Smad2; however, TGF‐β signalling also activates numerous serine/threonine kinases that phosphorylate Smad2 in its linker region. The expression of phosphorylated Smad linker proteins were determined following TGF‐β stimulation in the absence and presence of different serine/threonine kinase inhibitors in vascular endothelial cells. Methods Proteins were quantified by Western blotting using specific antibodies to individual phosphorylated Smad2 linker region residues. Key findings TGF‐β mediated the phosphorylation of all four Smad2 linker region residues of interest. Erk and Jnk specifically phosphorylate Ser245 while all mitogen‐activated protein kinases phosphorylate Ser250 and Ser255. Thr220 and Ser245 are phosphorylated by phosphoinositide 3 kinase (PI3K), while Ser255 was phosphorylated by the PI3K/Akt pathway. CDK and GSK‐3 were shown to phosphorylate Thr220 and Ser245. TGF‐β also mediated plasminogen activator inhibitor‐1 gene expression that was attenuated by p38 and CDK inhibitors. Conclusions TGF‐β‐mediated phosphorylation of individual serine/threonine sites in the linker region of Smad2 occurs in a highly specific manner by kinases. These phosphorylations provide an opportunity to further understand a therapeutically targeted and very specific signalling pathway in vascular endothelial cells.